2022
DOI: 10.1063/5.0096732
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tunable WGM lasing in a metal-dielectric core–shell hybrid microcavity

Abstract: We present a hybrid cavity designed to manipulate lasing modes, consisting of a metal-dielectric core–shell hybrid microcavity fabricated using a simple brush-coating method. Single and multiple modes can be obtained in the proposed laser device by the trade-off between loss and gain. Moreover, we achieve electrically tunable whispering-gallery-mode lasing by employing the thermo-optic effect in the hybrid microcavity. The lasing peak of the modes can be electrically tuned by quantitative control of Joule heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Reproduced with permission. [ 74 ] Copyright 2022, AIP publishing. d) Lasing wavelength changes as the increasing nanoparticle size in WGM‐random hybrid microcavity.…”
Section: Contribution Of Hybrid Microcavity To Laser Outputmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 74 ] Copyright 2022, AIP publishing. d) Lasing wavelength changes as the increasing nanoparticle size in WGM‐random hybrid microcavity.…”
Section: Contribution Of Hybrid Microcavity To Laser Outputmentioning
confidence: 99%
“…potential applications in soft matter photonic microlasers. As shown in Figure 2b, Wang et al embedded the organic/inorganic hybrid perovskite CH 3 NH 3 PbI 3 into the FP-DBR hybrid microcavity in 2018 [73] with the light emission showing a red shift from 751 to 758.6 nm with the temperature decreasing from 75 to 25 K. Recently, our group made a metal-dielectric core-shell hybrid microcavity (Figure 2c) by using simple brush coating method, [74] and realized electrically tunable WGM laser by using the thermooptic effect in the hybrid microcavity. By controlling the heating time or heating voltage in the metal-dielectric core-shell hybrid microcavity, the wavelength can be continuously adjusted in the range of 1.2 nm.…”
Section: Wavelength Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some researchers have shown that electronically tunable distributed feedback (DFB) lasers can be achieved through electroactive dielectric elastomer actuators [ 35 ] and III–V InGaAsP tuning layers [ 36 ]. To date, there have been a few studies on WGM electrical tuning; microstructural fibers based on dual-frequency liquid crystal (DFLCs) [ 37 ] and metal-dielectric core–shell hybrid microcavities with thermo-optical effects [ 38 ] provide WGM tuning schemes for wavelength shifting by applied electric fields.…”
Section: Introductionmentioning
confidence: 99%